Symbiotic germination of threatened Australian terrestrial orchids and the effect of nursery potting media on seedling survivals - Wright, Magali (Universidad de Costa Rica, 2015)
Since the early 1990s, the RBG has contributed to the conservation of Victoria’s Endangered orchids through its ex situ propagation program. Working cooperatively with the Victorian Department of Sustainability and Environment (DSE), the Melbourne Zoo, the Australasian Native Orchid Society, The University of Melbourne, RMIT University and Parks Victoria, research and development has lead to a greater understanding of Victoria’s terrestrial orchids and their associated mycorrhizal fungi, and assisted in the implementation of Recovery Plans.